The impact of stratospheric aerosol injection: a regional case study - Cohen, Sabrina L., author; Hurrell, James W., advisor; Keys, Patrick W., committee member; Lombardozzi, Danica L., committee member (Colorado State University. Libraries, 2025)
The detrimental effects of anthropogenic climate change have become ubiquitous as global greenhouse gas emissions concentrations continue to increase. As a result, research into proposed climate intervention (CI) techniques to offset some of the most damaging effects of climate change is increasing, with the idea that CI could provide more time for humanity to pursue decarbonization. One of the most researched CI techniques is stratospheric aerosol injection (SAI), which would reflect a small portion of sunlight away from Earth to reduce or lower temperature increases. While many studies have analyzed SAI's potential global impacts on climate variables, such as temperature and precipitation, relatively few have examined regional impacts on variables more intimately tied to human well-being, such as crop productivity. Thus, using climate model data, we analyze the projected impacts of one future climate change and three SAI scenarios on four Global South regions already socioeconomically vulnerable to climate change: South Asia (SAS), East Asia (EAS), South Central America (SCA), and West Africa (WAF). We find that, in the SAI scenarios, heat extremes are reduced and wet season precipitation, soil moisture and crop productivity increase relative to the climate change scenario in all four regions. Further, SAI clearly ameliorates crop productivity losses produced by climate change in WAF and SCA, with less clear benefits in SAS and EAS. Our study indicates the potential for SAI (in the scenarios examined here) to alleviate some of climate change's adverse impacts on human welfare.